2009
DOI: 10.1136/thx.2009.113795
|View full text |Cite
|
Sign up to set email alerts
|

Validation and clinical implications of the IDSA/ATS minor criteria for severe community-acquired pneumonia

Abstract: Background: The 2007 Infectious Disease Society of America (IDSA)/American Thoracic Society (ATS) guidelines defined severe community-acquired pneumonia (CAP) and recommended intensive care unit (ICU) admission when patients fulfilled three out of nine minor criteria. These criteria have not been validated. Methods: All patients admitted to our hospital from 2004 to 2007 for CAP were reviewed retrospectively. Patients who fulfilled any IDSA/ATS major criteria for severe CAP at the emergency department (ie, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
89
3
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(108 citation statements)
references
References 32 publications
9
89
3
7
Order By: Relevance
“…A criterion not impacting in low-mortality-rate institutions might be important for places where mortality is high (19). The overall 30-day mortality was 1.3% in the current study, whereas they were 14.7% in Phua's study (9), 9% in Lim's study (15) and 3.6% in Liapikou's study (16). The mortalities in the current and Liapikou's studies were low, which might explain the lack of an association of hypotension with mortality.…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…A criterion not impacting in low-mortality-rate institutions might be important for places where mortality is high (19). The overall 30-day mortality was 1.3% in the current study, whereas they were 14.7% in Phua's study (9), 9% in Lim's study (15) and 3.6% in Liapikou's study (16). The mortalities in the current and Liapikou's studies were low, which might explain the lack of an association of hypotension with mortality.…”
Section: Discussioncontrasting
confidence: 46%
“…Lim's international derivation and validation study revealed that the weight of each of the CURB-65 criteria were 8.1, 5.6, 1.7, 2.4 and 5.5, respectively (15), which were different from that currently reported. Liapikou et al (16) and Phua et al (9) discovered that confusion, urea >7 mmol·L -1 , respiratory rate ! 30-minutes -1 and low blood pressure were of unequal weight in predicting hospital mortality and that confusion had the strongest association with mortality when validating the IDSA/ATS minor criteria for severe CAP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To eliminate confounding by nosocomial complications, we excluded patients who were admitted to the ICU .72 h after presentation at the ED. Some patients were included in a separate study conducted [2004][2005][2006][2007]; this previous study, however, included non-critically ill patients and excluded those who were intubated or started on vasopressors in the ED [11]. The present study was approved by our institutional review board.…”
Section: Study Populationmentioning
confidence: 99%
“…Part of the problem is that while patients who require emergent mechanical ventilation and/or vasopressors (defined by the IDSA/ATS as major criteria for severe CAP) and hence direct ICU admission may easily be identified [2], clinical findings at the ED which suggest a rapidly progressive pneumonia are often more subtle. Accordingly, numerous clinical criteria for severe CAP requiring ICU admission have recently been proposed [3,9,10], including the IDSA/ATS minor criteria [1,11,12].…”
mentioning
confidence: 99%